The preclinical pharmacokinetics of Tolinapant—A dual cIAP1/XIAP antagonist with in vivo efficacy - Vanessa Martins; George Ward; Tomoko Smyth; Mike Reader; Gianni Chessari; Chris Johnson; Nicola Wilsher (Pharmacology Research & Perspectives)
Abstract AT‐IAP (1‐{6‐[(4‐fluorophenyl)methyl]‐3,3‐dimethyl‐1H,2H,3H‐pyrrolo[3,2‐b]pyridin‐1‐yl}‐2‐[(2R,5R)‐5‐methyl‐2‐{[(3R)‐3‐methylmorpholin‐4‐yl]methyl}piperazin‐1‐yl]ethan‐1‐one) was identified as a novel potent non‐alanine small molecule dual inhibitor of cIAP1/XIAP protein. AT‐IAP was assessed in preclinical species, demonstrating favorable bioavailability in rodent species and oral efficacy at 30 mg/kg in MDA‐MB‐231 mouse xenograft models. The major metabolic route of AT‐IAP was identified to be CYP3A driven, resulting in low oral exposure in non‐human primate (NHP) studies, given the comparatively high expression of equivalent CYP3A. AT‐IAP metabolite identification studies determined ring opening of the morpholino or piperazine moiety. An extensive campaign of optimisation resulted in increased polarity by the addition of a hydroxymethyl, which led to the identification of tolinapant (1‐(6‐[(4‐Fluorophenyl)methyl]‐5‐(hydroxymethyl)‐3,3‐dimethyl‐1 H,2 H,3 H‐pyrrolo[3,2‐ b]pyridin‐1‐yl)‐2‐[(2 R,5 R)‐5‐methyl‐2‐([(3R)‐3‐methylmorpholin‐4‐yl]methyl)piperazin‐1‐yl]ethan‐1‐one) with reduced CYP3A metabolism. Tolinapant showed oral bioavailability in rodents and NHP in the range 12–34% at 5 mg/kg. Non‐linear pharmacokinetics in NHP were observed at oral doses in the range 5–75 mg/kg. Pharmacodynamic modulation and efficacy were demonstrated in A375 mouse xenograft models at dose ranges between 5 and 20 mg/kg. On‐target engagement, as measured by reduction of cIAP 1 protein levels, was confirmed in NHP surrogate tissues and applied to target activity assessments in tolinapant phase1/2 clinical trials.